2021
DOI: 10.1192/bjo.2021.928
|View full text |Cite
|
Sign up to set email alerts
|

Managing returns to prison from medium-secure services: qualitative study

Abstract: Background Little is known about factors that influence discharge decision-making for people admitted to medium-secure services from prison, particularly for those who are returned to prison following treatment. Aims To explore the organisational influences on care pathways through medium-secure services for those admitted from prison. Method We recruited 24 clinicians via purposive and snowball sampling; 13 shared their experiences via a focus group, and 11 shared thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…We also conducted a subsequent qualitative investigation with clinicians working in forensic psychiatric services to understand discharge decision-making for individuals admitted from and returned to prison ( 15 ). Clinicians shared the context of constraints in which they operate and the ways in which they perceive these constraints.…”
Section: Introductionmentioning
confidence: 99%
“…We also conducted a subsequent qualitative investigation with clinicians working in forensic psychiatric services to understand discharge decision-making for individuals admitted from and returned to prison ( 15 ). Clinicians shared the context of constraints in which they operate and the ways in which they perceive these constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Leonard et al (2020) found that 28% of remitted patients were sent back to prison because they were assessed as ‘not engaging with treatment’ or because they were too high risk to remain in a medium secure unit. But a subsequent study confirmed that they had not been referred to high secure services (Leonard 2021). They also found that remittal to prison resulted in a loss of access to aftercare, for example several of their cohort were remitted close to their earliest release date or parole eligibility date, and they questioned why these patients did not remain in the medium secure unit to be released from there, which may well have ensured a more successful discharge to the community.…”
Section: Early Release Risk and Community Managementmentioning
confidence: 99%
“…Flows into prisons are influenced by experience of both the school system (Mallett 2016) and the care system (Day, Bateman, and Pitts 2020). Once under the supervision of the criminal justice system, people are transferred through distinct carceral institutions-for example, to and from police custody-and frequently secure mental health facilities (Leonard, Sanders, and Shaw 2021) and immigration detention (BiD 2013). Each new environment requires the detainee to familiarize themselves with a different set of expectations, challenges, rules, personnel, and oversight bodies.…”
Section: Reconceiving Carceral Harms: a Transcarceral Approachmentioning
confidence: 99%